Small and Medium-Size Enterprises (SMEs) & Risk Management: What distinguished success from failure for two SMEs with respect to their approach to risk - Ioannou, Constantinos (2015)
This project was written in order to find out how two firms in my country operated and the reasons why one succeeded and the other one failed. The analysis was done solely by primary research. Four people from each organization participated in the interviews. I conducted a qualitative research, which included interviews, based on the following businesses: a) P.A.E.E.K.: A sport facility b) Curves: A Gym line only for women